Bernstein-type inequalities for splines defined on the real axis - Babenko, V. F.; Zontov, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We obtain the exact inequalities of the Bernstein type for splines $s \in S_{m, h} \bigcap L_2 (\mathbb{R})$ as well as the exact inequalities that, for splines $s \in S_{m, h}, \quad h > 0$, estimate $L_p$-norms of the Fourier transforms of their $k$-th derivative by $L_p$-norms of the Fourier transforms of splines themselves.